1997
DOI: 10.1021/jp970009w
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio and DFT Potential Energy Surfaces for Cyanuric Chloride Reactions

Abstract: Ab initio and nonlocal density functional theory (DFT) calculations were performed to determine reaction mechanisms for formation of the six-membered ring C3N3Cl3 (cyanuric chloride) from the monomer cyanogen chloride (ClCN). MP2 geometry optimizations followed by QCISD(T) energy refinements and corrections for zero-point energies for critical points on the potential energy surface were calculated using the 6-31G* and 6-311+G* basis sets. DFT (B3LYP) geometry optimizations and zero-point corrections for critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Numerous studies comparing these methods now exist in the literature (for example, see refs −5). Recent studies have shown that approximate functionals take into account most of the dynamical and static electron correlation effects, thus producing descriptions of molecular spectroscopic properties of comparable quality to more expensive correlated methods. Relatively few comparative studies, however, have been performed to locate transition states and predict reaction paths . Such investigations are highly desirable in order to establish the limitations of DFT methods across wide regions of the molecular potential energy surface before subsequent dynamics simulations are performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies comparing these methods now exist in the literature (for example, see refs −5). Recent studies have shown that approximate functionals take into account most of the dynamical and static electron correlation effects, thus producing descriptions of molecular spectroscopic properties of comparable quality to more expensive correlated methods. Relatively few comparative studies, however, have been performed to locate transition states and predict reaction paths . Such investigations are highly desirable in order to establish the limitations of DFT methods across wide regions of the molecular potential energy surface before subsequent dynamics simulations are performed.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Relatively few comparative studies, however, have been performed to locate transition states and predict reaction paths. 10 Such investigations are highly desirable in order to establish the limitations of DFT methods across wide regions of the molecular potential energy surface before subsequent dynamics simulations are performed. Moreover, it is important to document the performance of DFT methods in describing a closed-shell system (singlet) and an open-shell counterpart (triplet) on an equal footing.…”
Section: Introductionmentioning
confidence: 99%
“…To understand why attempts to make 2 directly from 1 and glyoxal have been unsuccessful, reaction coordinate mapping was used to examine the reaction of both 1 and 4 with glyoxal . The results are shown in Figures and .…”
Section: Resultsmentioning
confidence: 99%
“…Generation and Fitting of the Atom-Atom Overlap Model. The calculations of the overlap and of the distributed multipoles 32 were carried out using a D 3h molecular structure, which was obtained by 3-21G SCF geometry optimization (and is almost identical to the 6-311+G MP2 optimized structure of Pai et al 36 ). A 6-31G* MP2 wave function of this structure was calculated using CADPAC.…”
Section: Methods Of Derivation Of the Intermolecular Potential Modelmentioning
confidence: 99%